Serpentine Soils, Adverse Habitat for Plants Case Study at Peninsular - Tashakor, Mahsa; Wan Yaacob, Wan Zuhairi; Mohamad, Hamzah (Science Publication, 2013)
The unpleasant effect of serpentine soil on plant life has been a topic of many studies for several decades. Infertility and flora selectivity nature of serpentine soils are the features, which made them of interest throughout the world. This research includes a geochemical study on two Malaysian serpentine massifs to introduce their harmful factors concerning vegetation. X-ray fluorescence results on 11 soil samples showed that serpentine soils comprise large values of iron and magnesium (up to 55 wt and 65 wt% respectively) and high amounts of some heavy metals like chromium (1248-18990 μg g-1), nickel (189-1692 μg g-1) and cobalt (95-478 μg g-1). However, soil extraction by ammonium acetate solution revealed that only magnesium is plant available. Besides, serpentine soils are poor in some major plant nutrients such as nitrogen, potassium and phosphorus. This substantial paucity is the main cause of bareness in these lands. Soils in the studied areas are moderately acidic and have the adequate cation holding capacity. Their Ca/Mg quotient is very low (less than 1). The latter with the low availability of the calcium (0.34 m-equiv 100 g-1 in average) is another challenging parameter in serpentine soils, which exerts negative influence on plant growing.